2016
DOI: 10.1590/1413-785220162404159372
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Study of the Nervous Communication Between the Median and Musculoucutaneous Nerve

Abstract: Objective: The aim of this study was to analyze the incidence of nerve communication between the musculocutaneous and median nerve. Methods: Anatomical dissection of 40 limbs from 20 fetal cadavers was performed at the Laboratory of Anatomy, Faculdade de Ciências Médicas e da Saúde da Pontifícia Universidade Católica de São Paulo. Results: A communicating branch was found in 10 upper limbs. In nine limbs there was a musculocutaneous-median anastomosis (type I); and in one limb there was a median-musculocutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
0
13
0
2
Order By: Relevance
“…All included studies were performed on cadavers. Among 20 studies that specified the age of cadavers (fetus or adult), five studies (Uysal et al, ; Kervancioglu et al, ; Woźniak et al, ; Reis et al, ; Caetano et al, ) dissected fetuses, one study (Guerri‐Guttenberg and Ingolotti, ) included both fetuses and adults, while 14 studies dissected only adult cadavers (Chiarapattanakom et al, ; Aktan et al, ; Choi et al, ; Beheiry, ; Loukas and Aqueelah, ; Pacha Vicente et al, ; Maheswari and Sadanandam, ; Pozo Kreilinger et al, ; Budhiraja et al, ; Sawant et al, ; Chaudhary et al, ; Ballesteros et al, ; Cambon‐Binder and Leclercq, ; Leng et al, ). Only in eight studies, the variations were described together with information about the sex of individual cadavers in whom they were encountered.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were performed on cadavers. Among 20 studies that specified the age of cadavers (fetus or adult), five studies (Uysal et al, ; Kervancioglu et al, ; Woźniak et al, ; Reis et al, ; Caetano et al, ) dissected fetuses, one study (Guerri‐Guttenberg and Ingolotti, ) included both fetuses and adults, while 14 studies dissected only adult cadavers (Chiarapattanakom et al, ; Aktan et al, ; Choi et al, ; Beheiry, ; Loukas and Aqueelah, ; Pacha Vicente et al, ; Maheswari and Sadanandam, ; Pozo Kreilinger et al, ; Budhiraja et al, ; Sawant et al, ; Chaudhary et al, ; Ballesteros et al, ; Cambon‐Binder and Leclercq, ; Leng et al, ). Only in eight studies, the variations were described together with information about the sex of individual cadavers in whom they were encountered.…”
Section: Resultsmentioning
confidence: 99%
“…The musculocutaneous nerve test was used as a surrogate test for the lateral cord, where the lateral pectoral nerve is of most interest. Since anastomoses between the median and musculocutaneous nerves 13 may interfere with sensory testing of the lateral cord, the lateral cord block was judged with both a sensory and a muscle power score.…”
Section: Methodsmentioning
confidence: 99%
“…This anatomical variation should be considered during the neurotization procedure of the musculocutaneous nerve for the restoration of elbow flexion. Caetano et al[4] (2016) observed in a study conducted on 40 specimens of upper limb that 10 specimens showed communication between median and musculocutaneous nerve. In the present study out of 72 specimens, four upper limbs showed communication between median and musculocutaneous nerve.…”
mentioning
confidence: 99%
“…Chouhan et al[8] 2002 India Case study -Sachdeva K. et al[9] 2011 India Case study -B. Caetano et al[4] 2016 Brazil 40 25…”
mentioning
confidence: 99%